Circular RNA Expression Profiling and Selection of Key Circular RNAs in the Hypothalamus of Heat-Acclimated Rats - Fan, Lijun; An, Gaihong; Wang, Shang; Chen, Xuewei; Liu, Ying; Liu, Zhifeng; Ma, Qiang; Wang, Jing (Frontiers in Physiology, 2019)
Circular RNAs (circRNAs) play crucial roles in diverse biological processes. However, expression levels and functions of circRNAs related to heat acclimation (HA) are poorly understood. we, for the first time, used comprehensive circRNA expression profiling to investigate circRNA–miRNA interactions in HA rats, to provide a better understanding of mechanisms underlying HA. CircRNA expression profile was performed in rats’ hypothalamus of HA and control group with microarray assays. Bioinformatics analysis was conducted to predict their functions. And differential circRNAs and their regulated downstream miRNAs and mRNAs were quantitatively validated using real-time quantitative polymerase chain reaction (RT-qPCR ). Predicted proteins expression were determined using enzyme-linked immunosorbent assay (ELISA). In total, 53 circRNAs were differentially expressed between the HA and C group; 28 of these circRNAs were upregulated, while 25 were downregulated in HA (Fold change >1.5; P < 0.05). Three circRNAs and two miRNAs and three predicted mRNAs were obviously regulated after validated by RT-qPCR in HA rats. Two proteins expression were proportional to their mRNA changes. Further analysis indicated the circRNAs mostly close to HA were grouped into 3 signal pathways: including rno_circRNA_014301-vs-rno-miR-3575-vs-Hif-1α, rno_circRNA_014301-vs-rno-miR-3575-vs-Lppr4, rno_circRNA_010393-vs-rno-miR-20b-3p-vs-Mfap4 in hypoxia response pathways, substance/energy metabolism and inflammatory response pathways. Our findings implicate that many circRNAs regulate expressions of genes that interact with each other to exert their functions during HA.